Leadership and Management: Case Studies in Training in Higher Education in Africa - Wildschut, Lauren; Mouton, J. (Johann) (Book collections on Project MUSE., 2015)
There has been a resurgence of interest in training programmes for higher education leaders and management (HELM) at African universities in recent times. Although there have been a few cases of evaluation studies of such programmes in Africa, a more systematic review of the lessons learnt through these programmes has not been done. This book aims to document and reflect on the learnings from intervention programmes at three African higher education councils. It is clear that university leaders face many leadership and management challenges. This is the starting point of the book.